Question #812fe

1 Answer
Mar 30, 2017

See the entire solution process below:

Explanation:

First, factor and cancel common terms for the fraction on the right:

(3ab) xx (2 xx 2)/(2a) -> (3ab) xx (color(red)(cancel(color(black)(2))) xx 2)/(color(red)(cancel(color(black)(2)))a) -> (3ab) xx 2/a

Next, multiply the two terms:

(3ab xx 2)/a -> (6ab)/a

Now, we can again cancel a common term in the numerator and denominator:

(6color(red)(cancel(color(black)(a)))b)/color(red)(cancel(color(black)(a))) -> 6b

However, from the original expression we cannot divide by 0 therefore the solution is:

6b where 2a != 0 or a != 0